Photochemical activity of PSII of tropical phytoplankton communities of Southern Brazil exposed to solar radiation and nutrient addition - Villafañe, Virginia Estela (2014)
We carried out short- and mid-term incubations to assess the combined impact of solar ultraviolet radiation (UVR, 280-400nm) and nutrient addition on tropical phytoplankton communities from BabitongaBay, Southern Brazil. Samples were collected at a station ~ 10km inward from the mouth i.e., Inlet, and incubated in microcosms under solar radiation at the surface of the water, with or without UVR, and under two nutrient conditions (ambient and with addition of macronutrients). Nutrient addition had the largest impact on specific growth rates, almost doubling the growth of algae as compared to ambient conditions. UVR-induced inhibition of the effective photochemical quantum yield (Y) at the initial conditions was higher at ambient nutrient conditions than in samples with nutrient addition, demonstrating the antagonistic effect among the two factors. Inhibition (k) and recovery (r) rates of Y at the beginning of the experiment suggest a high sensitivity of this community, but they were reduced after 4 days of exposure in the microcosms, hinting for the presence of acclimation mechanisms. Also, differences in taxonomic composition, with increasing dominance of diatoms in nutrient-enriched cultures, as compared to the initial time and in ambient nutrient conditions (with higher proportion offlagellates) may account for the observed variability in responses along the time as well as within treatments.